Diplomacy Review of Delegation of Republic of Indonesia to the International Civil Aviation Organization in Montreal Canada - Afen Sena; Ahmad Hariri; Genny Luhung Prasojo; Prasetyo Iswahyudi (SKYHAWK : Jurnal Aviasi Indonesia, 2021)
The International Civil Aviation Organization (ICAO) is an important institution that mandates the world's civil aviation authorities to play a role in reforming Standards and Recommended Practices (SARPs) of civil aviation. SARPs are the main reference for all parties related to the issue of international civil aviation. Indonesia's relationship and cooperation with the ICAO is therefore, important and should be a priority. ICAO is an organization where Indonesia is able to protect and defend its national interests. Relations and cooperation with ICAO are priorities in order to help and improve Indonesian civil aviation safety and security. This study was based on observations made by the Permanent Delegation of Republic of Indonesia on the diplomatic role played in ICAO during 2020 by studying the latest aspects of ICAO governing bodies, development of specific issues, pending issues and follow-up of Indonesia diplomatic role in ICAO. In general, the aim of the diplomatic role in ICAO is focused on supporting the achievement of three items; 1) securing Indonesia's national interest in international civil aviation cooperation; 2) support international civil aviation programs and issues that are ICAO's priority; and 3) improve Indonesia's position in ICAO, especially in order to prepare for Indonesia's candidacy to the ICAO Council.